(untitled) (Research, Society and Development, 2021)
Bezoars are solid structures found in the gastrointestinal tract, they are formed by aggregation of non-digestible material resulting from repeated ingestion, may having a nucleus hair or fur. Causing signs presented of obstructive processes, intussusception, enteropathies and perforations, generally, their signs are nonspecific and depends on the location and degree of obstruction. Thus, the present work aims to report the presence of a gastric trichobezoar in a specimen of collared peccary (Pecari tajacu) raised in captivity. The animal comes from the Center for Multiplication in Wild Animals (CEMAS) of the Federal Rural University of the Semi-Arid (UFERSA) and make part of a project, in this project should be done the gestational monitoring, being necessary the accomplishment of ultrasound, however, with the examination, no structures compatible with the principles were observed, but during the physical examination, a mass of firm consistency was felt in the abdominal region. As a control measure, the animal was euthanized and performed a necroscopic examination. Upon accessing the abdominal cavity, it was possible to notice the altered volume in the stomach and the presence of a foreign body, with a circular shape, and with a subsequent incision of the gastric chamber, the presence of an oval structure, covered with material vegetable and with the presence of fur in the nucleus, this nucleus had a color ranging from green to shades of black. Through these findings and together with the bibliographic survey, it is concluded that it is a gastric trichobezoar.